Установление времени строительства (перестройки) Надымского городка: дендрохронологический аспект - Омурова, Г.Т.; Баринов, В.В.; Кардаш, О.В.; Мыглан, В.С.; Omurova, Gulzar T.; Barinov, Valentin V.; Kardash, Oleg V.; Myglan, Vladimir S. (Сибирский федеральный университет. Siberian Federal University., 2013)
This work is devoted to the application of dendrochronological methods to establish the time of construction and reconstruction of the archaeological monument named Nadymsky gorodok where located 60 km to the north-north-west from the town of Nadym, Yamal-Nenets autonomous area, Tyumen region. We discussed aspects related to the building of tree-ring chronologies of different tree species and their cross-dating and relation with calendar periods. The next periods of construction (reconstruction) of Nadymsky gorodok were distinguished: the third decade of the XV century, middle of seventh – beginning of eighth decade of the XV century, end of XV – beginning of XVI century, the third or fourth decade of the XVI century, the first quarter of the XVII century. Generalized tree-ring chronology of Nadymsky gorodok was built and covered the period from 1010 to 1616 AD Статья посвящена вопросам применения дендрохронологического метода для установления времени сооружения и перестройки археологического памятника – Надымского городка. Рассмотрены методические аспекты, связанные с построением древесно-кольцевых хронологий по разным древесным породам, их перекрестной датировке и календарной привязке. Полученные результаты позволили установить периоды сооружения (перестройки) анализируемого памятника: второе–третье десятилетия XV в., середина седьмого – начало восьмого десятилетия XV в., конец XV – начало XVI столетия, третье-четвертое десятилетия XVI в., первая четверть XVII в. – и построить обобщенную древесно-кольцевую хронологию «надым», отражающую многолетнюю изменчивость годичного прироста древесной растительности в среднем и нижнем течении р. Надым